HYPERTENSION EFFECTS ON THE DECREASED KIDNEY FUNCTION PROGRESIVITY IN BENIGN PROSTATIC HYPERPLASIA PATIENTS - Dhiemas Trisyuananda Eniestama; Aziz, Ayu Munawaroh; Wahyudi, Septa Surya (Indonesian Journal of Urology, 2021)
Objective: A comprehensive knowledge about BPH and hypertension is needed to reduce morbidity and mortality in patients with decreased kidney function due to the two diseases. Material & Methods: This research used the observational analytics method with cross-sectional design. This research used secondary data from medical records of BPH patients in Bina Sehat Hospital and Paru Hospital from January 1st to December 1st 2019. Results: Comparative serum creatinine test results in hypertensive BPH patients with non-hypertensive BPH patients using the Mann Whitney test, obtained p= 0.000. Based on these results it can be concluded that there are significant differences in serum creatinine between hypertensive BPH patients and non-hypertensive BPH patients. Correlation test results using the Spearman test between serum creatinine with blood pressure systole and diastole all samples obtained each p= 0.000 r= 0.399 for systolic blood pressure and p= 0.000 r= 0.337 for diastole blood pressure. Based on these results it can be concluded that there is a significant correlation between serum creatinine with systolic and diastolic blood pressure of the patient. Conclusion: Hypertension will worsen the kidney function decline in BPH patients seen from an increase in serum creatinine.